2021
DOI: 10.3390/rs13224640
|View full text |Cite
|
Sign up to set email alerts
|

Fractal Characteristic Analysis of Urban Land-Cover Spatial Patterns with Spatiotemporal Remote Sensing Images in Shenzhen City (1988–2015)

Abstract: Understanding the urban land-cover spatial patterns is of particular significance for sustainable development planning. Due to the nonlinear characteristics related to the spatial pattern for land cover, it is essential to provide a new analysis method to analyze them across remote sensing imagery. This paper is devoted to exploring the fractals and fractal dimension properties of land-cover spatial patterns in Shenzhen city, China. Land-cover information was extracted using a supervised classification method … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 60 publications
2
9
0
Order By: Relevance
“…Considering that the FD estimate for the floodplain of the MPR corresponded to an extraordinary flood such as the one in 1983, and an average low water level in 2001, the FD value should be understood as an extreme value for each hydrological phase. The FD values obtained in this study are in agreement with those identified by Cheng et al (2021), who calculated the FD values of water bodies in Shenzhen city in different years.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…Considering that the FD estimate for the floodplain of the MPR corresponded to an extraordinary flood such as the one in 1983, and an average low water level in 2001, the FD value should be understood as an extreme value for each hydrological phase. The FD values obtained in this study are in agreement with those identified by Cheng et al (2021), who calculated the FD values of water bodies in Shenzhen city in different years.…”
Section: Discussionsupporting
confidence: 92%
“…Authors such as, Klinkenberg and Goodchild (1992), Mandelbrot (1983), Nikora (1991), and Zhang et al (2015) have demonstrated that the FD is connected to geomorphological complexity. However, in line with Cheng et al (2021), our study verified that FD can be calculated using the water surface area at different water levels to detect the different floodplain patterns. A key aspect of this study is that the FD parameter allowed us to spatially discretize the role of the floodplain in the hydrodynamics of the MPR and in attenuating hydrological events.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Shenzhen presents a “low west and high east” situation, with an elevation span of 5 m in the west to 944 m in the east. The topographic relationship determines that the urban area of Shenzhen is mostly located in the west, while eastern Shenzhen is dominated by mountains and low hills (Cheng et al., 2021).…”
Section: Study Area and Data Setsmentioning
confidence: 99%